Effect of fecal microbiota transplantation in children with autism spectrum disorder: A systematic review - Jing Zhang; Jing Zhang; Jing Zhang; Gang Zhu; Gang Zhu; Gang Zhu; Lin Wan; Lin Wan; Lin Wan; Yan Liang; Yan Liang; Yan Liang; et al. (Frontiers in Psychiatry, 2023)
BackgroundFecal microbiota transplantation (FMT) may be helpful in the treatment of autism spectrum disorder (ASD) as rebalancing the gut microbiome has been shown to potentially improve behavioral symptoms in children with ASD.MethodsThis systematic review was conducted to assess the effect of FMT for children with ASD. The Embase, PubMed, Web of Science, and Cochrane Library databases were searched for articles published from inception to October 6, 2022. Two reviewers independently screened the identified records and undertook data extraction.ResultsThe search identified a total of five studies: two prospective open-label studies, two retrospective observational studies, and a case report; however, no randomized controlled trial was identified. All five studies reported a significant post-FMT-treatment improvement in neuropsychological assessment of ASD. The two prospective open-label studies suggested that the Autism Behavior Checklist (ABC) score, and the Social Responsiveness Scale (SRS) score at the posttreatment assessment decreased from the baseline (Wilcoxon signed-rank test; all p < 0.01]). The two retrospective observational studies suggested that FMT helped to improve the ASD symptoms. One observational study reported that the Childhood Autism Rating Scale (CARS) score and ABC score of the constipation group decreased from the baseline after the second course assessment (CARS [baseline: mean 35.25 ± standard deviation 4.36, second course: 32.5 ± 3.1, p = 0.015]; ABC [baseline: 56.21 ± 16.08, second course: 46.54 ± 16.54, p = 0.046]). Another observational study found that both ABC and CARS scores decreased as the number of FMT courses increased, and significant differences were found at the end of each course as compared with the baseline.ConclusionCompared with the baseline, FMT significantly improved symptoms of autism in children with ASD in observational studies. However, rigorously designed randomized controlled clinical trials are needed to establish the safety and efficacy of FMT as a treatment for ASD.